Metastatic clear cell renal cell carcinoma demonstrating intense uptake on 68Ga-DOTATATE positron emission tomography: Three case reports and a review of the literature - Nadebaum, David; Lee, Sze; Nikfarjam, Mehrdad; Scott, Andrew (World Journal of Nuclear Medicine, 2018)
68Ga-DOTATATE positron emission tomography (PET) is a molecular imaging technology which has shown superiority over 111In-octreotide scanning for the detection and staging of neuroendocrine tumors. We report three patients with pancreatic masses that were ultimately diagnosed as clear cell renal cell carcinoma (ccRCC) metastases on histopathology. During their initial diagnostic assessment, the three patients underwent both 18F-fluorodeoxyglucose (18F-FDG) and 68Ga-DOTATATE PET. While all three patients' lesions showed variable 18F-FDG avidity, uptake on 68Ga-DOTATATE PET was comparatively intense. The small case series illustrates the need to consider ccRCC in the differential diagnosis of 68Ga-DOTATATE avid lesions.
Keywords: 68Ga-DOTATATE; kidney neoplasms; positron emission tomography; renal cell carcinoma; somatostatin receptors